Three decades later: The fate of the population of patients who underwent the Atriopulmonary Fontan procedure. (15th March 2017) - Poh, Chin Leng; Zannino, Diana; Weintraub, Robert G.; Winlaw, David S.; Grigg, Leeanne E.; Cordina, Rachael; Hornung, Tim; Bullock, Andrew; Justo, Robert N.; Gentles, Thomas L.; Verrall, Charlotte; du Plessis, Karin; et al.
Abstract: Objective: To review our experience of patients with an atrio-pulmonary Fontan circulation to determine their long-term outcomes. Methods and results: A retrospective analysis of long-term follow-up data using the Australia and New Zealand Fontan Registry was performed. There were 215 patients surviving hospital discharge after an atrio-pulmonary Fontan completion. A total of 163 patients were alive at latest follow-up, with 52 deaths. Twelve patients had required heart transplantation and 95 had Fontan failure (death, transplantation, Fontan takedown, Fontan conversion, severe systemic ventricular dysfunction or NYHA ≥ 3). Twenty-eight year freedom from death, death and transplantation and Fontan failure were 69% (95% CI 61–78%), 64% (95% CI 56–74%) and 45% (95% CI 36–55%) respectively. One hundred and thirty patients developed atrial arrhythmias. Freedom from arrhythmia at 28 years post Fontan was 22.9% (95% CI: 15.1–30.8). Development of arrhythmia increased the likelihood of death (HR:2.97, 95%CI 1.50–5.81; p = 0.002), death and heart transplantation (HR:3.11, 95%CI 1.64–5.87; p < 0.001) and Fontan failure (HR:4.78 95%CI 2.95–7.74; p < 0.001). There were 42 patients who had thromboembolic events, of which only 12 were therapeutically anti-coagulated. Two-thirds of the surviving patients (86/126) with an intact atrio-pulmonary Fontan were regularly reviewed. Patients receiving follow-up care with general cardiologists without specialised training were more likely to face Fontan failure than those managed by cardiologists with specialist training in congenital heart disease (HR: 1.94, 95% CI 1.16–3.24; p = 0.02). The majority of the surviving patients (81/86) remained physically active and almost two-thirds (54/86) were currently employed. Conclusion: Two-thirds of the patients who underwent a classical atrio-pulmonary Fontan are still alive 3 decades later. The majority are affected by the burden of arrhythmias but remain functionally active today. These challenging patients should only receive follow-up care from cardiologists with specialised training.